Travel vloggers' information quality and credibility on Bangladeshi's destination choice with perceived information adoption as mediators - Md Tariqul, Islam (2023)
Travel vlogs are considered as a video form of online review, which is usually generated by tourists and shared most on social media platforms. Travel vlogs have emerged as a significant source of information on tourist products and services, including information regarding tourist destinations, accommodation, cuisine, touristic activities, mode of accessibility, etc. Moreover, travel vlogs are the updated version of word of mouth (WoM), where the tourist provides a review or share their experience regarding the products or services that they have consumed. The current study has been conducted to identify how the information quality of travel vlog videos and vlogger credibility influence the Bangladeshi social media users’ destination choice with the mediating role of information diagnosticity, information usefulness, information trust, and information adoption. The conceptual framework of the present study is an extension of the Information Adoption Model. The present study has been conducted based on the positivism paradigm, and it is a quantitative study. Data were obtained by surveying 231 Bangladeshi social media users with a structured, self-administered, close-ended questionnaire. The data has been collected through purposive and snowball sampling techniques. Two statistical software have been employed for data analysis purposes; SPSS (v.26) and Smart PLS (v.3.3.9). SPSS software has been used for screening the data, cleaning the data, treating the missing data, respondents' demographic profile analysis, and correlation analysis. Smart PLS software has been used for identifying the construct validity, reliability, discriminant validity, and Structural Equation Modeling (SEM). The current study's findings indicate that travel vlog information quality and vlogger credibility have a significant relationship with information diagnosticity, information usefulness, and information trust. In addition, information diagnosticity, information usefulness, and information trust have a significant relation with information adoption as well as information adoption had a significant relationship with destination choice. Moreover, information diagnosticity, information usefulness, information trust, and information adoption mediate the relationship of travel vlog information quality and vlogger credibility with destination choice. In addition, the present study provides both theoretical and practical contributions. Theoretically, the current study extends the Information Adoption Model (IAM) with three variables; information diagnosticity, information trust, and destination choice. Whereas all the stakeholders of the tourism industry of Bangladesh will be benefitted from the practical contributions of the present study. Finally, the study has been concluded by indicting several limitations and recommendations for future research.